2020
DOI: 10.33024/jkm.v6i2.2409
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Hubungan Tingkat Pendidikan Ibu Dan Pendapatan Keluarga Dengan Kejadian Stunting Pada Anak Usia 6-59 Bulantingkat Pendidikan Ibu Dan Pendapatan Keluarga Dengan Kejadian Stunting Pada Anak Usia 6-59 Bulan Di Desa Mataram Ilir Kecamatan Seputih Surabaya Tahun 2019

Abstract: ABSTRAK Latar Belakang : Stunting adalah kondisi gagal tumbuh pada anak balita (bayi di bawah lima tahun). Di Indonesia, berdasarkan hasil Riskesdas tahun 2013 terdapat 37,2% balita yang mengalami stunting, hal ini mengalami peningkatan dibandingkan hasil Riskesdas tahun 2010 yaitu sebesar 35,6%. Ada 100 kabupaten/kota di Indonesia yang angka kejadian stuntingnya paling besar dan menjadi prioritas penangannya oleh pemerintah. Dan 3 diantaranya terdapat di Provinsi Lampung yaitu Lampung Selatan 43.01%, Lampung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
34

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 0 publications
3
15
0
34
Order By: Relevance
“…The results showed that the education of mothers who had children with stunting was 71% at the junior high school level, then there was a significant relationship with the incidence of stunting, namely  (0.03) <  (0.05). This was confirmed by the reserched of Mataram that there was a significant association between maternal education level with the incidence of stunting and low maternal education 3.313 times higher risk of experienced stunting with high maternal education (Nurmalasari, Anggunan and Febriany, 2020) The level of mother's education had a big influenced on the nutritional status of the family which had an impact on family health, especially for children, because mothers are the main supervisors in food management and have an important role in improved the nutritional status of children. (Noviyanti, Rachmawati and Sutejo, 2020).…”
Section: Discussionmentioning
confidence: 68%
“…The results showed that the education of mothers who had children with stunting was 71% at the junior high school level, then there was a significant relationship with the incidence of stunting, namely  (0.03) <  (0.05). This was confirmed by the reserched of Mataram that there was a significant association between maternal education level with the incidence of stunting and low maternal education 3.313 times higher risk of experienced stunting with high maternal education (Nurmalasari, Anggunan and Febriany, 2020) The level of mother's education had a big influenced on the nutritional status of the family which had an impact on family health, especially for children, because mothers are the main supervisors in food management and have an important role in improved the nutritional status of children. (Noviyanti, Rachmawati and Sutejo, 2020).…”
Section: Discussionmentioning
confidence: 68%
“…Previous research stated that the most dominant factor causing stunting in children aged 24-59 months is the level of education of Ibu 6 . Another study also stated that there is a relationship between the level of maternal education and the incidence of stunting in children 7 .…”
Section: Introductionmentioning
confidence: 95%
“…Hal ini sesuai dengan penelitian yang dilakukan Husnaniyah dkk (2020) yang menyatakan bahwa terdapat hubungan antara tingkat pendidikan ibu dengan kejadian stunting di wilayah kerja Puskesmas Kandanghaur Indramayu (10). Penelitian Nurmalasari dkk (2020) juga menyatakan terdapat hubungan yang bermakna antara tingkat pendidikan ibu dengan kejadian stunting dengan kejadian stunting pada anak usia 6-59 bulan di Desa Mataram Ilir Kecamatan Seputih Surabaya Lampung Tengah (11). Penelitian Tiwari, et al (2014) menunjukkan hal yang sama bahwa pendidikan ibu berhubungan dengan kejadian stunting balita.…”
Section: Pembahasanunclassified